Investment Feasibility Analysis in Financial Aspects of Noor Halal Minimarket Business Development Over Islamic Schools - Ferry Pantjoro Prihambodo; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Diana Fajarwati (Penerbit Kemala Indonesia, 2020)
PT. Noor Halal is a company who engaged retail sector by opening minimarkets in several Islamic Education Institutions, especially over Islamic Boarding Schools, Bogor, West Java. Science, January 2017 to December 2019, this company has 9 (nine) outlets with untapped market niche, especially in West Java Province because it has a large number of Islamic boarding school (Pesantren) especially Bogor District was chosen as a development location after seeing the potential number of Pesantren and student around 1,060 building and 71,750 people, respectively. The mainstay strategy in this company is use vending machine innovations by day-to-day operations for efficiency and application of tiered prices following a certain number of purchases. In this study the investment feasibility analysis is done by calculating and analyzing the parameters namely ROI, P, BEP, PP, and IRR with a corporate investment plan with 11.18 billion IDR also indicating that the investment is feasible to run. The investment feasibility analysis of several parameters was achieved by ROI in 5th year achieved with positive and significant growth reaching 25%; NPV calculated with a WACC interest rate of 13.21% with positive results; BEP or breakeven point will be reached within 1 year 10 months and The resulting IRR rate is 60.79%, respectively.